Fortalecimiento de la imagen corporativa y posicionamiento de “QualityDental” en el mercado de la ciudad de Cuenca 2022 - Asitimbay Loaiza, Libia Fernanda (2023)
This thesis was carried out in order to improve the corporate image and positioning of QualityDental in Cuenca city, allowing to increase its value in customers and achieve its identification in the population. According to the demands of the competitive market, the need arises to establish the best corporate image strategies for QualityDental, which becomes an element to motivate its employees, who feel proud of the brand for which they work, getting more involved in the work processes and developing their potential to the maximum. For the purposes of the same, Quantitative Research was used and through the instruments in a sample, the results that support the initiative to improve its image were obtained, to attract more professionals and future professionals, ensuring that the purchase there is not only a good experience, but that they prefer it among some dental deposits and obtain loyalty in current customers who although it is true know certain products that the companies market, but they do not know in their entirety the services provided by QualityDental. This proposal is based on creating a branding plan that includes the identification and promotion of the values and organizational culture of the company, establish strategies aimed at improving the relationship with the client, based onpropose a new technical service that meets the expectations of customers, create a training plan for workers in such a way that they develop the skills for customer service and Implement incentives for salespeople who manage to increase sales and customer base Finally, the respective conclusions and recommendations for implementing the project are shown. Keywords: Corporate Identity, brand positioning, market, sales strategies.